Pengaruh Harga terhadap Loyalitas Pelanggan Studi Kasus pada Antavaya Tour and Travel Jakarta - Sofiani Marcelline Hartono (JURNAL NASIONAL PARIWISATA, 2023)
The Travel Bureau is one of the supporters that makes it easy for the public to access various information and transportation that supports tourist trips. The high level of tourism travel in Indonesia with easy access for the community, especially the emergence of a travel agency that makes it easier for the public to access various information and transportation that supports tourism travel. The existence of online transactions also helps boost sales of travel agents as well as helping the country's economy. The method used in this study is a quantitative method that is associative and explanatory with primary data by distributing questionnaires to 100 respondents. The analytical method used is simple linear regression analysis, validity test, reliability test, classic assumption test which consists of a normality test, linearity test, and hypothesis testing, namely the T test and the coefficient of determination test. The results of the study indicate that there is a significant positive effect of price on customer loyalty at AntaVaya Tour & Travel by 55.7% and the remaining 44.3% is influenced by other variables not examined in this study. The conclusion in this study is that price has an influence on customer loyalty so that Antavaya Tpur and Travel should pay attention to price and also other aspects such as service quality, facilities, ease of ordering, and so on. For other researchers, it is better to add other variables besides price in influencing customer loyalty.